Tsenguluso ya kushumisele kwa mirero na maidioma kha vhafumakadzi kha manwala a Netshivhuyu na Sigogo - Mudau, Thivhulawi Sarah (University of Limpopo, 2015)
Refer to document
Thesis (M. A. (African Languages)) -- University of Limpopo, 2015
Keywords: Tsonga idioms; Tsonga (African people); Tsonga language (idioms)